2006
DOI: 10.1177/1090198105284875
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the “TrEAT Yourself Well” Restaurant Nutrition Campaign

Abstract: This study examined the effect of the "TrEAT Yourself Well" campaign on diners'menu choices using data from four restaurant chains in California. Within each chain, two locations in the greater San Diego area were selected as experimental sites and either one or two locations outside the greater San Diego area were selected as control sites. Various promotional activities, including in-restaurant promotions, community events, and paid media advertising, were conducted in the experimental region to promote heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 32 publications
(51 reference statements)
1
38
0
Order By: Relevance
“…Results also suggest that the Choose Health LA Restaurants program successfully increased the availability of reduced-size portions for adults and healthier menu options for children in participating restaurants. These findings are complemented by previous research which has shown high levels of support for voluntary restaurant recognition programs from restaurant owners (Nevarez et al, 2013) and patrons (Acharya et al, 2006), supporting the potential value of such efforts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Results also suggest that the Choose Health LA Restaurants program successfully increased the availability of reduced-size portions for adults and healthier menu options for children in participating restaurants. These findings are complemented by previous research which has shown high levels of support for voluntary restaurant recognition programs from restaurant owners (Nevarez et al, 2013) and patrons (Acharya et al, 2006), supporting the potential value of such efforts.…”
Section: Discussionsupporting
confidence: 81%
“…Establishing the level of compliance is an important first step to demonstrating program impact -i.e., improvements made to expand healthy food access and forecasts of program features that are adopted and can be sustained over time. To date, the primary focus of research and evaluation of these programs has been on stakeholder experience and perceptions and patron reaction and awareness (Acharya, Patterson, Hill, Schmitz, & Bohm, 2006;Macaskill et al, 2000). Less is known about the menu changes that are made to comply with program criteria.…”
Section: Introductionmentioning
confidence: 98%
“…This area is challenging as the benefits (better health via healthy eating) are temporally distant, which may devalue it in comparison to a competing or habitualized behaviour offering immediate satisfaction or reward. Studies in the current review with clear examples of exchange offered immediate benefits in the form of food samples (35,37) , coupons (36) , vouchers (24) , prizes (24,38,39) through to extra time off (21) .…”
Section: Exchangementioning
confidence: 99%
“…Incentives in the form of product trials, rewards and prizes were offered for trial or repeat behaviour (21,24,35,36) . An exchange between two parties (the marketer and the consumer) is an important concept in the social marketing framework, and to be effective the consumer must believe that he/she will get as much or more than he/she gives (7) .…”
Section: Exchangementioning
confidence: 99%
“…In our study, food establishments represented a critical means to involve not only individuals but also families in healthy lifestyles at a reasonable price. The cost of dishes is an important factor affecting consumer choice in restaurants [24]. …”
Section: Discussionmentioning
confidence: 99%